Pediatric Procedural Skills Training Curriculum - Taylor Sawyer; Kevin Creamer; Robert Puntel; John Lin; Daniel Steigelman; Joseph Lopreiato; Mark Thompson (Association of American Medical Colleges, 2010)
Abstract This resource is a training curriculum on pediatric procedural skills. It was developed as a yearly procedural skills training day, which allows incoming interns the opportunity to practice several of the required Accreditation Council for Graduate Medical Education pediatric procedural skills on patient simulators prior to performing the procedures on real patients. The curriculum includes a slide-show presentation and a procedural skills checklist, which can be used as evidence of procedural competency. Much of the literature devoted to pediatric simulation training has focused on simulation technology and the effectiveness of simulation-based education. Relatively little has been published on simulation curricula. Here, we present a detailed pediatric procedural skills simulation curriculum that has been designed for use in pediatric graduate medical education programs. Preliminary feedback from residents who have experienced the training is encouraging. Efforts are currently underway to collect outcome data on the effectiveness of the training. The authors hope this curriculum will help others who wish to implement a procedural skills simulation curriculum within their training program.